About consciousness: dialogue with to Arno Engelmann - Simão, Lívia Mathias (Paidéia (Ribeirão Preto), 2002)
This paper arises from a semiotic-constructivist reflective exercise respect to some central features of Arno Engelmann´s theoretical formulations about consciousness. First, some of the main Engelmann´s proposals about the focused subject are summarized. Following and in counterpart, some nuclear semiotic-construtivist proposals addressing to the subject-reality relationship , which can be viewed as establishing a dialogue with the previously Engelmaniann formulations, are highlighted. Last but not least, some questions respect to the Engelmann´s approach to consciousness followed from that dialogue are set to be discussed.